Rippling relacionado a una variante en el gen CAV3 en un niño peruano: reporte de caso - Saavedra Ruiz, Maira (2026)
Background: Caveolinopathies are diseases primarily caused by variants in the CAV3 gene (caveolin-3), affecting skeletal muscle, cardiac muscle, or both. Case description: We describe the case of a 6-year-old Peruvian boy who presented with muscle stiffness, myalgia, rippling, and hyperCKemia. Clinical examination revealed calf hypertrophy, Achilles tendon contractures, and toe walking. Next-generation sequencing analysis identified the previously reported heterozygous pathogenic variant c.99C>G (p.Asn33Lys) in CAV3. Segregation studies in affected family members were consistent with an autosomal dominant inheritance pattern. Conclusions: This case illustrates the phenotypic variability of caveolinopathies and highlights the importance of considering this diagnosis in patients with myalgia and rippling beginning in the first decade of life. Although clinical findings guide the diagnosis, genetic confirmation is necessary to provide timely family counseling.